Impact of prior melphalan exposure on stem cell collection in light chain amyloidosis. (March 2018) - Sidana, Surbhi; Tandon, Nidhi; Gertz, Morie; Dispenzieri, Angela; Buadi, Francis; Lacy, Martha; Dingli, David; Fonder, Amie; Hayman, Suzanne; Hobbs, Miriam; Gonsalves, Wilson; Hwa, Yi; et al.
Abstract Use of melphalan in multiple myeloma was observed to have a deleterious effect on stem cell collection in older studies. There is limited data on the impact of melphalan in light chain (AL) amyloidosis, especially in the plerixafor era. We retrospectively evaluated stem cell mobilization in 610 patients with AL amyloidosis, of which 79 had prior exposure to melphalan, 167 to other chemotherapeutics, while 364 had no chemotherapy exposure. Collection of CD34+ stem cells × 106 /kg was lower in the melphalan group. Median total yields in the melphalan, non-melphalan, and no chemotherapy groups were 5.5, 7.7, and 7.8, respectively;p  < 0.001. Day-1 yields were 2.7, 3.5, and 4.0 (p  = 0.0003), respectively, and median yields per collection were 2.0, 3.3, and 4.0 (p  < 0.001), respectively. Similar results were observed in the sub-group analysis after plerixafor was integrated in our collection algorithm (2009). Patients in the melphalan group had higher failure rate of 9% vs. 2% each in the other two groups (p  = 0.006). Impact of melphalan was dose-dependent, with cumulative melphalan exposure of >150 mg (median: three cycles) resulting in lower yields. Therefore, duration of melphalan exposure prior to stem cell collection should be limited, ideally, not exceeding more than two cycles of treatment.